Difference in the complications between colonoscopy and esophagogastroduodenoscopy in Japan using a large-scale health insurance claims data - Naohisa Yoshida; Hideki Ishikawa; Michihro Mutoh; Naoto Iwai; Reo Kobayashi; Ken Inoue; Ryohei Hirose; Osamu Dohi; Yoshito Itoh; Azusa Yoda; Ayako Maeda-Minami; Yasunari Mano (Endoscopy International Open)
Background and study aims: Analyses of colonoscopy (CS) and esophagogastroduodenoscopy (EGD) complications is crucial for further promoting the use of endoscopy. This study analyzed the rates of severe complications of CS compared to those of EGD using big data. Patients and methods: As a study population, we retrospectively used commercially anonymized health insurance claims data covering 3,050,954 patients from January 2010 to December 2020. Patients ≥50 years old who underwent CS or EGD without treatment were included in the study. The main outcomes were the difference in rates of hemorrhage, perforation, and fatal events between EGD and CS, and the risk factors of each complication comparing CS to EGD. Results: Among 290,470 CSs (male: 182,910, female: 107,560, median age [range]: 58 [50-75]) and 726,075 EGDs (male: 412,365, female: 313,710, 58 [50-75]), the rates of hemorrhage, perforation, and fatal events for EGD and CS were 0.0069% vs. 0.0069% (p=0.558), 0.0006% vs. 0.0024% (p=0.008), and 0.00028% vs. 0.00034% (p=0.648), respectively. The rates of hemorrhage for cases 50-64 and 65-75 years old were 0.0059% vs. 0.0110% (p=0.042) for EGD and 0.0061% vs. 0.0108% for CS (p=0.264). The risks of hemorrhage (adjusted odds ratio [95% confidence interval]) for comparing CS to EGD were significant for biopsy (2.75 [1.15-6.21], p=0.017) and antithrombotics (12.48 [1.80-247.14], p=0.026). Those of perforation were significant for age 50-64 (9.58 [2.17-66.10], p=0.006) and male (11.76 [1.85-222.65], p=0.025). Conclusions: Compared to EGD, CS showed a higher rate of perforation but not hemorrhage. Complication rates in CS did not differ by age.